1999
DOI: 10.1117/12.348519
|View full text |Cite
|
Sign up to set email alerts
|

<title>Motion analysis of artery pulsation in neonatal cranial ultrasonogram</title>

Abstract: Using an optical-flow technique, we have quantitatively analyzed tissue motion due to artery pulsation accompanied with blood flow in a neonatal cranial ultrasonogram. The tissue motion vector was successfully calculated at each pixel in a series of echo images (32 frames, 640x480 pixels/frame, 8 bits/pixel, 33 ms/frame) taken in the brightness mode by using an ultrasound probe of 5.0MHz. The optical-flow technique used was a gradient method combined with local optimization for 3 x 3 neighbors. From two-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The cranial ultrasound image sequence of a newborn baby is taken as noisy, speckle-like gray scale image including non-rigid tissues such as cerebrums and arteries with local motion due to artery pulsation of blood flow [2]. Therefore, the tissue-motion may vary with time and place.…”
Section: Ultrasound Image Tissue-motion Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cranial ultrasound image sequence of a newborn baby is taken as noisy, speckle-like gray scale image including non-rigid tissues such as cerebrums and arteries with local motion due to artery pulsation of blood flow [2]. Therefore, the tissue-motion may vary with time and place.…”
Section: Ultrasound Image Tissue-motion Estimationmentioning
confidence: 99%
“…The scan ultrasound image sequences are not only use for real-time diagnosis but also recorded for future diagnosis. Pediatricians use an ultrasonogram to find the cranial abnormalities in a newborn baby, since they can observe the brain tissue through the anterior fontanel [2,5]. A key point of diagnosis is whether there is the artery pulsation accompanied with blood flow or not [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The B-mode cranial ultrasound images were taken as movie and recorded with a video tape at neonatal intensive care unit by a conventional ultrasonograph apparatus with the ultrasound probe of 5~7MHz. It was reported that the sway of the ultrasound probe and/or the movement of newborn baby head may cause artefacts of strong pulsation and that the poor optimization of brightness and contrast may decrease the sensitivity of tissue motion [4]. The visualization procedure is shown Fig.…”
Section: Fourier Analysis Of Tissue-motionmentioning
confidence: 99%
“…Instead of using pixel value, optical flow with local optimization is used in [4]. The strength of artery pulsation of asphyxiated neonates such as hypoxic ischemic encephalopathy (HIE) babies were discuss in [5] by using optical flow method.…”
Section: Introductionmentioning
confidence: 99%